102k views
5 votes
Drag each equation to show if it could be a correct first step to solving the equation 2(x+7) =36

Drag each equation to show if it could be a correct first step to solving the equation-example-1

2 Answers

7 votes

Answer:

Here you go

Explanation:

Drag each equation to show if it could be a correct first step to solving the equation-example-1
User Federico Galfione
by
5.5k points
3 votes

Answer:

(2.x) + (2.7) = 36

Explanation:

Solving the given equation with the distributive property,

A(B + C) = (A.B) + (A.C)

So that,

2(x+7) = 36

(2.x) + (2.7) = 36

2x + 14 = 36

2x = 36 - 14

2x = 22

x = 11

From the given expressions, the option that is the correct first step to solving this equation is;

(2.x) + (2.7) = 36

User Frazer Kirkman
by
5.7k points